PREVENCIÓN DEL DELITO Y CONSTRUCCIÓN DE FEMINIDADES JUVENILES - Medan, Marina (Universidad de Costa Rica, 2013)
This article seeks to articulate age and gender dimensions within the female client construction in a crime prevention program, implemented in Gran Buenos Aires, Argentine. It identifies how girls are managed in a state intervention, targeted to youth people but specially on boys. The institutional legitimacy of female needs has an influence on the way girls configure their gender identity and on their own young and female experience.